2013
DOI: 10.1007/s00198-013-2394-6
|View full text |Cite
|
Sign up to set email alerts
|

Ankle fractures have features of an osteoporotic fracture

Abstract: Ankle fracture had features of osteoporotic fracture that is characterized by age- and gender-dependent low bone attenuation. Ankle fracture should not be excluded from the clinical and research interest as well as from the benefit of osteoporosis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…Reduced, normal and increased BMD have all been reported in patients with ankle fracture [19][20][21][22]. Some studies [23,24] have demonstrated a decrease in the incidence of ankle fractures in women after the age of 60 years; however, in a large study [25] of 91 490 ankle fractures, of which 57% had occurred in women, an agerelated increase in incidence rate was seen in women but not in men.…”
Section: Key Pointsmentioning
confidence: 95%
“…Reduced, normal and increased BMD have all been reported in patients with ankle fracture [19][20][21][22]. Some studies [23,24] have demonstrated a decrease in the incidence of ankle fractures in women after the age of 60 years; however, in a large study [25] of 91 490 ankle fractures, of which 57% had occurred in women, an agerelated increase in incidence rate was seen in women but not in men.…”
Section: Key Pointsmentioning
confidence: 95%
“…We did not limit our outcomes to study only fractures because of limited trauma, as work has shown that high‐trauma fractures are associated with low bone mineral density and therefore a higher risk of subsequent fracture particularly among older adult populations . Ankle fractures, though sometimes not considered in studies of osteoporotic fractures, were included here because these fractures have features of osteoporotic fractures that are subject to age and sex‐dependent low bone attenuation . We chose these fracture sites in part based on results from a prior validation study at KPWA (unpublished).…”
Section: Ascertainment Of Fracturementioning
confidence: 99%
“…In a recent CT study of 194 ankles, elderly patients showed more complex fracture patterns and significantly higher bone attenuation than the younger age group, suggestive of osteoporosis. 20 Routine osteodensitometry and adequate medication after confirming the diagnosis of osteoporosis are mandatory in the management of these patients.…”
Section: Osteoporosismentioning
confidence: 99%